2007
DOI: 10.1007/s00213-007-0896-7
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter binding after recovery from eating disorders

Abstract: Divergent 5-HTT activity in subtypes of eating disorder subjects may provide important insights as to why these groups have differences in affective regulation and impulse control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 76 publications
3
63
0
Order By: Relevance
“…While 5-HTT levels in AN and AN-BN individuals are comparable to controls (Table 1), 5-HTT differences have been observed when AN and AN-BN subgroups are compared. 57 These findings may be consistent with a recent study 58 showing that the S-allele of the 5-HTTLPR (serotonin-transporter-linked polymorphic region in SLC6A4) genotype increases the risk susceptibility for diagnostic crossover over time in ill subjects.…”
Section: Alterations In the Serotonergic Systemsupporting
confidence: 91%
“…While 5-HTT levels in AN and AN-BN individuals are comparable to controls (Table 1), 5-HTT differences have been observed when AN and AN-BN subgroups are compared. 57 These findings may be consistent with a recent study 58 showing that the S-allele of the 5-HTTLPR (serotonin-transporter-linked polymorphic region in SLC6A4) genotype increases the risk susceptibility for diagnostic crossover over time in ill subjects.…”
Section: Alterations In the Serotonergic Systemsupporting
confidence: 91%
“…41 The results suggested that (1) EDs, AN and BN, have neurobiological traits due to persistent disturbance of 5-HTT function, and 2) there are changes in serotonergic function among subtypes of EDs in different brain areas regulating mood and impulse control. Integration of imaging and genetic studies will provide clear direction for understand- ing genetic vulnerability to dysfunction in neural circuits related to EDs.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, stress has been shown to downregulate serotonin receptors in the raphe nuclei [42]. Depletion of central serotonin is also found in several psychiatric disorders including obsessivecompulsive disorder (OCD) [43], depression [44], eating disorders [45], and anxiety disorders [46]. Accordingly, attachment-related anxiety is thought to increase insecure feelings towards the relationship with a partner.…”
Section: Discussionmentioning
confidence: 99%